The Traverse Ridge Paleoseismic Site and Ruptures Crossing the Boundary Between the Provo and Salt Lake City Segments of the Wasatch Fault Zone, Utah, United States - Toké, Nathan A.; Phillips, Joseph; Langevin, Christopher; Kleber, Emily; DuRoss, Christopher B.; Hiscock, Adam I.; McDonald, Greg N.; Wells, Jack D.; Carlson, J. Kade; Horns, Daniel M. (Frontiers in Earth Science, 2021)
How structural segment boundaries modulate earthquake behavior is an important scientific and societal question, especially for the Wasatch fault zone (WFZ) where urban areas lie along multiple fault segments. The extent to which segment boundaries arrest ruptures, host moderate magnitude earthquakes, or transmit ruptures to adjacent fault segments is critical for understanding seismic hazard. To help address this outstanding issue, we conducted a paleoseismic investigation at the Traverse Ridge paleoseismic site (TR site) along the ∼7-km-long Fort Canyon segment boundary, which links the Provo (59 km) and Salt Lake City (40 km) segments of the WFZ. At the TR site, we logged two trenches which were cut across sub-parallel traces of the fault, separated by ∼175 m. Evidence from these exposures leads us to infer that at least 3 to 4 earthquakes have ruptured across the segment boundary in the Holocene. Radiocarbon dating of soil material developed below and above fault scarp colluvial packages and within a filled fissure constrains the age of the events. The most recent event ruptured the southern fault trace between 0.2 and 0.4 ka, the penultimate event ruptured the northern fault trace between 0.6 and 3.4 ka, and two prior events occurred between 1.4 and 6.2 ka (on the southern fault trace) and 7.2 and 8.1 ka (northern fault trace). Colluvial wedge heights of these events ranged from 0.7 to 1.2 m, indicating the segment boundary experiences surface ruptures with more than 1 m of vertical displacement. Given these estimates, we infer that these events were greater than Mw 6.7, with rupture extending across the entire segment boundary and portions of one or both adjacent fault segments. The Holocene recurrence of events at the TR site is lower than the closest paleoseismic sites at the adjacent fault segment endpoints. The contrasts in recurrence rates observed within 15 km of the Fort Canyon fault segment boundary may be explained conceptually by a leaky segment boundary model which permits spillover events, ruptures centered on the segment boundary, and segmented ruptures. The TR site demonstrates the utility of paleoseismology within segment boundaries which, through corroboration of displacement data, can demonstrate rupture connectivity between fault segments and test the validity of rupture models.